2010
DOI: 10.1158/0008-5472.can-10-0833
|View full text |Cite
|
Sign up to set email alerts
|

H3K9 Histone Methyltransferase G9a Promotes Lung Cancer Invasion and Metastasis by Silencing the Cell Adhesion Molecule Ep-CAM

Abstract: G9a is a mammalian histone methyltransferase that contributes to the epigenetic silencing of tumor suppressor genes. Emerging evidence suggests that G9a is required to maintain the malignant phenotype, but the role of G9a function in mediating tumor metastasis has not been explored. Here, we show that G9a is expressed in aggressive lung cancer cells, and its elevated expression correlates with poor prognosis. RNAi-mediated knockdown of G9a in highly invasive lung cancer cells inhibited cell migration and invas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
311
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(329 citation statements)
references
References 41 publications
14
311
3
1
Order By: Relevance
“…Indeed, overexpression of G9a is associated with several types of cancers and downregulation of G9a by RNAi inhibits tumor cell proliferation. [7][8][9] Chaetocin and BIX-01294 are small molecules that inhibit histone H3K9 HMTs. Chaetocin, which inhibit both G9a and Suv39h activities, is a member of the epipolythiodioxopiperazine (ETP) class of fungal metabolites.…”
mentioning
confidence: 99%
“…Indeed, overexpression of G9a is associated with several types of cancers and downregulation of G9a by RNAi inhibits tumor cell proliferation. [7][8][9] Chaetocin and BIX-01294 are small molecules that inhibit histone H3K9 HMTs. Chaetocin, which inhibit both G9a and Suv39h activities, is a member of the epipolythiodioxopiperazine (ETP) class of fungal metabolites.…”
mentioning
confidence: 99%
“…Unmodified H3 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] peptide (23 μM) was incubated with 25 nM G9a-SET in the presence of 50 μM SAM (radioactive: nonradioactive molar ratio = 0.016) in a buffer containing 50 mM Hepes (pH 7.9), 0.5 mM DTT, 0.25 mM PMSF, and 2 mM MgCl 2 . Where applicable, different H3 1-20 K9X peptides (Tufts University Peptide Synthesis Core) were present in the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies identified a role for G9a in heterochromatin maintenance and transcriptional repression, such as the silencing of repeat elements, including long interspersed nuclear elements and endogenous retroviruses (12)(13)(14). Up-regulation of both G9a and G9a like protein (GLP) has implications in a variety of human cancers, including solid tumors as well as acute myeloid leukemia (15)(16)(17). Here, we present biochemical and structural evidence that the histone H3K9M peptide inhibits G9a activity by effectively competing with WT histone H3 substrate peptide for binding to the active site.…”
mentioning
confidence: 99%
“…Similarly, HP1a expression is upregulated in various tumor tissues in contrast to the corresponding normal tissues without detectable HP1a expression, as well as in highly malignant breast cancers with poor patient survival (De Koning et al 2009). In addition, HP1-related methyltransferase G9a has been reported to promote lung cancer invasion and metastasis (Chen et al 2010). In addition, we have recently shown that HP1b is upregulated with an increased Gleason score in prostate cancer (Shiota et al 2010a).…”
Section: Discussionmentioning
confidence: 93%